EFFECT OF NIGELLA SATIVA SEEDS ON GROWTH, NUTRIENTS DIGESTIBILITY AND SOME BLOOD METABOLITES IN MALE BEETAL GOATS - S.Ahmed; R. Mahmood; A. R. Muhammad; I. Mohsin; G. A. Chishti; M. Q. Javed (Journal of Animal and Plant Sciences, 2022)
Aim of study was to evaluate the effects of Nigella sativa seeds (NSS) supplementation on growth performance, digestibility and selected blood metabolites of male Beetal goats. Fifteen male Beetal goats were randomly divided into three groups A, B and C according to Completely Randomized Design. Group A male Beetal goats served as control and fed basal diet only whilst group B and C male Beetal goats were fed separately 5 and 10 g NSS respectively in form of total mixed ration having a crude protein 15.6% and ME 2.63 Mcal /g, along with the basal diet for a period of sixty days. Data were statistically analyzed through one-way ANOVA followed by least significant difference test. Average daily gain (ADG), feed efficiency (FE) and dry matter intake (DMI) were affected by NSS. Male Beetal goats fed C and B (NSS based diet) had greater ADG and FE than the male Beetal goats fed A (control diet). Male Beetal goats fed C had greater DMI than the male Beetal goats fed A. Total tract DM, CF and CP digestibility were also affected by NSS. Male Beetal goats fed C and B had greater DM and CP digestibility than the male Beetal goats fed A. For CF, male Beetal goats fed C had greater digestibility than the male Beetal goats fed A. Blood plasma cholesterol and triglyceride were both affected by NSS. Male Beetal goats fed B and C had lesser plasma cholesterol and triglyceride than the Male Beetal goats fed A. In conclusion, 10 g NSS can be used in male Beetal goats’ diet to improve their growth performance and digestibility.
Keywords: Digestibility; Male Beetal goats; Nigella sativa seeds; Growth